The Problems of Learning Arabic at Madrasah Ibtidayyah - Norhidayah Norhidayah; Aulia Mustika Ilmiani; Nor Anisa Siska; Nurlaila (IAI Muhammadiyah Sinjai, 2023)
The purpose of this study is to analyze the problems of learning Arabic in class I madrasah ibtidayyah students at the integrated madrasah ibtidayyah